Achieving a realistic utopia: Rawls, realization, and the task of political philosophy - Terlazzo, Rosa Elizabeth (Rhodes University, Faculty of Humanities, Department of Philosophy, 2010)
In this thesis I argue that the tradition of political philosophy which follows in John Rawls's footsteps is obligated to concern itself not only with the realizability, but also with the realization, of justice. Although Rawls himself expresses a commitment only to the former of these, I argue that the roles which he assigns to political philosophy require him to take on the further commitment to realization. This is because these roles are meant to influence not only political philosophers, but the citizens of the wider community as well. The realistically utopian role, which I take to be the central one, requires political philosophy to inspire in that population a hope which I argue that realizability alone cannot provide. Given the deep revisions regarding the political nature of justice as fairness which Rawls made on the basis of realizability concerns, I argue that his theory must in this case be committed to a similar revision. The hope which political philosophy is meant to provide is simply not realizable until the discipline concerns itself centrally with the task of realization.
Keywords: Rawls, John, 1921-2002; Political science -- Philosoph; Justice -- Philosophy; Utopias -- Philosophy